Taking issue with how the Work-integrated Learning discourse ascribes a dualistic meaning to graduate employability - Björck, Ville (Higher education, 2021)
Work-integrated Learning (WIL) is renowned for providing a bridge between ‘theory’ and ‘practice’ that fosters ‘employable graduates’. This study critically argues that the WIL discourse continues to ascribe a dualistic meaning to graduate employability that primarily contributes to creating the so-called theory–practice gap for students. As an argument towards such a conclusion, a genealogical discourse analysis of how the graduate employability idea operates in 87 present and past official documents concerning the Cooperative Education (Co-op) WIL model is used. Two accounts of graduate employability, the antagonistic practice acclaiming account and the harmonious theory and practice account, recur in both the present and past documents. Both accounts contribute to creating the gap, while the latter also contributes to bridging it. The non-dualistic account, which involves knowing that the key to becoming employable is understanding how both research-based and informal theory shape daily occupational work, could be a useful alternative to these accounts. This is because it could encourage students to see how theory is a form of knowledge manifested in, rather than disconnected from, this work. However, the usual WIL design, whereby universities and workplaces outside universities are respectively institutionalised as the places where ‘theory’ and ‘practice’ is learnt, is not so much instrumental in spreading this non-dualistic account, but rather implies to students that ‘theory’ is absent from daily work until they apply it. Thus, I discuss how establishing physical and/or virtual countersites to the usual WIL design could potentially spread this account to students.